The effect of various titanium dioxide [TiO2] loading on polymorphism of stretched polyvinylidene flouride [PVDF] /TiO2 thin film / Zulkhairul Akmal Abdul Basir - Abdul Basir, Zulkhairul Akmal (2020)
The composite of Polyvinylidene Fluoride/ Titanium dioxide (PVDF/TiO2) thin film were prepared with various loading of TiO2 using solvent casting method. The solution was stirred for 48 hours using magnetic stirrer at 600rpm. The mixture was casted into glass petri dish before being dried in the oven for 1 hour at 115 oC until the thin film sample formed. Then, the sample was transformed into dumbbell shape and stretched in 3 minutes. The necking area or the stretching area were studied using micrometer screw gauge, inverted microscopy, differential scanning calorimetry (DSC) and ATR-FTIR. The thickness of the thin film was increasing significantly with the addition of TiO2. Same goes to the Tensile strength, Incorporated TiO2 in the PVDF able to enhance the mechanical properties significantly. As for the surface morphology, whitening oval occurs at the control which indicates the lamella while crystal nuclide of TiO2 was formed and tend to increase with the amount TiO2 used. Next, on the DSC, the melting temperature (Tm) increased with addition of TiO2 and PVDF10 shows the highest degree of crystallinity. Lastly, on the ATR-FTIR, PVDF10 has been identified to have highest β-phase due increase the β and γ phase to the second highest peak at 1168cm-1 region, able to increase the β-phase at 1401 cm-1 and most importantly it has the highest peak on 834 cm-1 regions which indicate also the β-phase. Overall, the incorporation of PVDF10 shows the best because it able to produce highest degree of crystallinity and the β-phase.